Evaluation of changes in neutrophil-lymphocyte ratio and platelet-lymphocyte ratio in patients with vitiligo (Annals of Medical Research, 2021)
Aim: Vitiligo is an acquired disease with loss of melanocytes, etiology of which is unclear. The aim of this study is to determine the role of systemic inflammation in vitiligo by measuring the Neutrophil-Lymphocyte ratio (NLR), platelet-lymphocyte ratio (PLR) markers included in routine hemogram test, in patients with vitiligo.Material and Methods: The study was carried out by reviewing the data of patients who applied to İnönü University Faculty of Medicine Dermatology Polyclinic and diagnosed with vitiligo after Wood’s lamp examination, between July 2012 and February 2018. The study was performed retrospectively by reviewing patient files and ethics committee approval was not obtained.Results: A total of 170 individuals including 79 vitiligo patients and 91 healthy individuals were included in the study. When the vitiligo patients and healthy control group were compared in terms of routine hemogram parameters, statistically significant differences were found in terms of erythrocyte distribution width (RDW), but there were no statistically significant differences in terms of NLR, PLR, lymphocyte, neutrophil, platelets and White bloodcell (WBC) counts.Conclusion: In our study, only RDW value was found to be higher in patients with vitiligo compared to healthy controls, and no difference was found in other parameters indicating systemic inflammation.
Keywords: Vitiligo; Platelet-Lymphocyteratio; Neutrophil-Lymphocyteratio; erythrocyte distribution width.